Three-dimensional structure of the LDL receptor-binding domain of the human apolipoprotein E2 (Arg136 → Cys) variant - Feussner, Giso; Albanese, Marco; Valencia, Alfonso (Atherosclerosis, 1996)
The familial lipoprotein disorder type III hyperlipoproteinemia (HLP) is usually inherited as a recessive trait. Indeed, more than 90% of affected individuals are homozygous for a receptor binding-defective isoform of apolipoprotein (apo) E, apo E2. However, some rare apo E variants have been described that dominantly (thus in a single dose) predispose to the disease. Amino acid substitutions, which are accompanied with the loss of positive charges within the proposed apo E binding-region to lipoprotein receptors, seem to be responsible in most of these cases for the dominance with respect to the expression of type III HLP. So far available data in the literature on the naturally occurring human apo E2 (Arg136 → Cys) variant are not conclusive about its recessive or dominant character. We recently identified a subject heterozygous for this mutation, presenting the typical clinical and biochemical characteristics of type III HLP. In the present study we performed further analysis of the mutation on apo E structure and function based on computer modeling. Our combined data point to a dominant influence of the apo E2 (Arg136 → Cys) variant with respect to the transmission of the disease.
Elektronische Reproduktion der Druck-Ausgabe 3. November 1997
Gesehen am 29.01.2025
Im Titel ist "136" tiefgestellt